Identification of a Novel Human Polyomavirus in Organs of the Gastrointestinal Tract - Korup, Sarah; Rietscher, Janita; Calvignac-Spencer, Sébastien; Trusch, Franziska; Hofmann, Jörg; Moens, Ugo; Sauer, Igor; Voigt, Sebastian; Schmuck, Rosa; Ehlers, Bernhard (PloS one, 2013)
Polyomaviruses are small, non-enveloped viruses with a circular double-stranded DNA genome. Using a generic polyomavirus PCR targeting the VP1 major structural protein gene, a novel polyomavirus was initially identified in resected human liver tissue and provisionally named Human Polyomavirus 12 (HPyV12). Its 5033 bp genome is predicted to encode large and small T antigens and the 3 structural proteins VP1, VP2 and VP3. Phylogenetic analyses did not reveal a close relationship to any known human or animal polyomavirus. Investigation of organs, body fluids and excretions of diseased individuals and healthy subjects with both HPyV12-specific nested PCR and quantitative real-time PCR revealed additional virus-positive samples of resected liver, cecum and rectum tissues and a positive fecal sample. A capsomer-based IgG ELISA was established using the major capsid protein VP1 of HPyV12. Seroprevalences of 23% and 17%, respectively, were determined in sera from healthy adults and adolescents and a pediatric group of children. These data indicate that the virus naturally infects humans and that primary infection may already occur in childhood.